1997
DOI: 10.1016/s1097-2765(00)80006-4
|View full text |Cite
|
Sign up to set email alerts
|

Complementation Cloning of , a Gene Encoding a Putative Metalloprotease Required for Intramembrane Cleavage of SREBPs

Abstract: We report the cloning of a gene, S2P, that encodes a putative metalloprotease required for intramembrane proteolysis of sterol-regulatory element-binding proteins (SREBPs) at Site-2. SREBPs are membrane-bound transcription factors that activate genes regulating cholesterol metabolism. The active NH2-terminal domains of SREBPs are released from membranes by sequential cleavage at two sites: Site-1, within the lumen of the endoplasmic reticulum; and Site-2, within a transmembrane segment. The human S2P gene was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
424
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(436 citation statements)
references
References 45 publications
11
424
0
1
Order By: Relevance
“…M19 cells in which the orthologous Mbtps2 is deleted cannot grow in cholesterol and lipid-deficient culture media. 13 Wild-type MBTPS2 stably transfected into the M19 cells complemented this defect and restored their wild-type growth characteristics. None of the five mutants detected in IFAP patients retained this property to the same extent as did the wild-type gene; however, great variation was observed in residual activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…M19 cells in which the orthologous Mbtps2 is deleted cannot grow in cholesterol and lipid-deficient culture media. 13 Wild-type MBTPS2 stably transfected into the M19 cells complemented this defect and restored their wild-type growth characteristics. None of the five mutants detected in IFAP patients retained this property to the same extent as did the wild-type gene; however, great variation was observed in residual activity.…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9][10][11][12] Oeffner et al 5 reported that IFAP syndrome is caused by functional deficiency of membrane-bound transcription factor protease, site 2, an intramembrane zinc metalloprotease that is essential for cholesterol homeostasis and the ER stress response. [13][14][15] They performed a linkage analysis involving two families of European descent, in which IFAP segregated according to an X-linked pattern of transmission, and assigned the IFAP locus to the 5.4-Mb region between DXS989 and DXS8019 on Xp22.11-p22.13. They identified five missense mutations exchanging highly conserved amino acids in MBTPS2 at Xp22.11 in five unrelated patients of European descent.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous signal peptide peptidases function in immunity by liberating signaling domains of TNFα and FasL (Fluhrer et al, 2006; Friedmann et al, 2006; Kirkin et al, 2007). Site-2 proteases are metalloenzymes that release transcription factors from the membrane to regulate membrane biogenesis and stress responses in diverse organisms from bacterial pathogens to man (Rawson et al, 1997; Makinoshima and Glickman, 2005). Lastly, rhomboid proteases act as prime regulators of signaling in insects by activating EGF signals through proteolytic shedding (Urban et al, 2001, 2002), and play prominent functions in diverse pathogen signaling and adhesion (Urban, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The M19 mutant of Chinese hamster ovary (CHO) cells is deficient in S2P (Hasan et al, 1994;Rawson et al, 1997). It was previously shown that M19 cells are unable to induce the expression of ERSE reporter gene or of the major ER chaperone BiP at either mRNA or protein levels in response to ER stress (Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%